Proceedings of the European Conference on Cognitive Ergonomics 2017 2017
DOI: 10.1145/3121283.3121304
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Psychological Reactance in Human-Computer Interaction

Abstract: Psychological reactance is a psychological effect that can reduce the acceptance of devices and services. So far, there has not been a collection of potential causes for reactance in the context of human-computer interaction in literature. A literature review and a qualitative study to compile a list of possible causes of reactance in human-computer interaction were conducted. The final list includes twelve causes of reactance that have been shown to appear in the field of human-computer interaction. The indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In the context of everyday interactions, factors such as intelligibility, control over a system, trust, likeability, or acceptance and expectations of the system are also shown to influence people's perception of autonomy or reactance (Sankaran and Markopoulos, 2021). An extensive literature review and survey in human-computer interaction showed that factors like undesirable behavior of agents, restricting choice, and control would lead to psychological reactance among users (Ehrenbrink and Prezenski, 2017). However, it is not clear how these factors influence people's perception of autonomy and reactance vary in different contexts.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of everyday interactions, factors such as intelligibility, control over a system, trust, likeability, or acceptance and expectations of the system are also shown to influence people's perception of autonomy or reactance (Sankaran and Markopoulos, 2021). An extensive literature review and survey in human-computer interaction showed that factors like undesirable behavior of agents, restricting choice, and control would lead to psychological reactance among users (Ehrenbrink and Prezenski, 2017). However, it is not clear how these factors influence people's perception of autonomy and reactance vary in different contexts.…”
Section: Motivationmentioning
confidence: 99%
“…Recent research states reactance as negative motivational arousal which is experienced by people when they experience a threat to or loss of free behavior and independent actions (Steindl et al, 2015 ). In human–computer interaction, factors such as reduced freedom of choice and behavior restriction cause psychological reactance when interacting with systems in real-life situations (Ehrenbrink and Prezenski, 2017 ). Furthermore, studies have shown that digital assistants influence users' perceived control during an interaction, often resulting in disappointment with the online recommendation (André et al, 2018 ) and experience a psychological reactance when they perceive that their freedom is reduced (Lee and Lee, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, when humans are subjected to persuasive attempts, they can respond to these attempts by showing both positive responses (liking, compliance) and negative responses (tantrum, reactance). Positive experiences include conformity to the robots by children [14], trustworthy to the robots with dissimilar gender with users [15] and increment of human performance facilitated by robot touch [16]. Indeed, powerful persuasive attempts can lead to psychological reactance [17] as highlighted earlier [18].…”
Section: Introductionmentioning
confidence: 99%
“…The weight of advice captures the distance to advice, but not reactance. Reactance to AI is a prevalent problem (Ehrenbrink and Prezenski, 2017;Sheng and Chen, 2020), and a mere assessment of the mean weight of advice may prove insufficient in effectively capturing these complex response patterns. Furthermore, various explanation strategies may elicit distinct levels of reactance.…”
Section: Accurate Information Strategiesmentioning
confidence: 99%